Analytically useful blue chemiluminescence from a water-soluble iridium(iii) complex containing a tetraethylene glycol functionalised triazolylpyridine ligand. Issue 7 (26th February 2016) - Smith, Zoe M.; Kerr, Emily; Doeven, Egan H.; Connell, Timothy U.; Barnett, Neil W.; Donnelly, Paul S.; Haswell, Stephen J.; Francis, Paul S.
Abstract : The first highly water soluble, blue-luminescent iridium(iii ) complex for chemiluminescence detection is presented. Abstract : We examine [Ir(df-ppy)2 (pt-TEG)] + as the first highly water soluble, blue-luminescent iridium(iii ) complex for chemiluminescence detection. Marked differences in selectivity were observed between the new complex and the conventional [Ru(bpy)3 ] 2+ reagent, which will enable this mode of detection to be extended to new areas of application.